On the Harmony between Epistemology and Pistology. Issue 1 (2nd January 2021) - Lebens, Samuel
ABSTRACT: In this paper I seek to retain many of Dormany's central claims about the excellent-making features of faith, without accepting her direct application of evidentialism to faith. In order to achieve that goal, I argue that we have to distinguish between the non-conflicting norms of (1) epistemology and (2) pistology. We also have to distinguish the often conflicting norms of epistemic and practical rationality.